The Relationship Between Class Climate And Citizen’ Participation In Learning Equality Package B in SPNF-SKB Region II Padang City - Wati, Rani Gusna; Solfema, Solfema (Universitas Negeri Padang, 2023)
The background to this research is the low participation of residents in the package B equality learning program at SPNF-SKB Region II Padang City. One of the suspected causes is that classroom conditions are less conducive for residents taking part in the program. The aim of this research is to see an overview of the classroom climate in package B equality learning at SPNF-SKB Region II Padang City. We also want to see a picture of student participation in package B equality. Apart from that, we want to know the relationship between classroom climate and learning participation in package B equality in SPNF-SKB Region II Padang City. In this research, a quantitative approach was used to carry out correlational analysis. In this research, the population studied was 72 people who were citizens studying package B equality in SPNF-SKB Region II Padang City. At the same time, the sampling technique used was stratified random sampling with a proportion of 50% (36). Data collection technique employs the distribution of questionnaires directly to the respondents. Percentage and product moment formulas are used in data analysis techniques. From the research conducted, it was found that the classroom conditions of students who used package B in studying equality were classified as unsupportive, and citizen participation in studying equality in package B tended to be low. Apart from that, there is a significant relationship between class conditions and student participation in package B equality learning at SPNF-SKB Region II Padang City. Tutor research findings suggest that the class atmosphere in Package B learning can be improved.Keywords: Clasroom Clite,, Participation, Learning Cittiziens